Eeyarestatin I inhibits Sec61-mediated protein translocation at the endoplasmic reticulum - Cross, Benedict C. S. (Company of Biologists, 2009)
Production and trafficking of proteins entering the secretory pathway of eukaryotic cells is coordinated at the endoplasmic reticulum (ER) in a process that begins with protein translocation via the membrane-embedded ER translocon. The same complex is also responsible for the co-translational integration of membrane proteins and orchestrates polypeptide modifications that are often essential for protein function. We now show that the previously identified inhibitor of ER-associated degradation (ERAD) eeyarestatin 1 (ES(I)) is a potent inhibitor of protein translocation. We have characterised this inhibition of ER translocation both in vivo and in vitro, and provide evidence that ES(I) targets a component of the Sec61 complex that forms the membrane pore of the ER translocon. Further analyses show that ES(I) acts by preventing the transfer of the nascent polypeptide from the co-translational targeting machinery to the Sec61 complex. These results identify a novel effect of ES(I), and suggest that the drug can modulate canonical protein transport from the cytosol into the mammalian ER both in vitro and in vivo.